(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the epidemiological and clinical characteristics of allergic conjunctivitis in patients ≤ 18 years old who presented for examination and treatment at Hanoi Medical University Hospital in 2025. Subjects and methods: A cross-sectional descriptive study was conducted on patients ≤ 18 years old diagnosed with allergic conjunctivitis in 2025. Demographic and clinical characteristics were collected and analyzed. Results: The study included 33 patients with a mean age of 9.33 ± 4.09 years (range 2-18 years). Males accounted for 78.8% of cases, and 57.6% lived in urban areas. Ocular itching was the most common symptom (81.8%), followed by eye rubbing (57.6%), redness, and blinking (27.3%). A total of 42.4% of patients presented within under 7 days of symptom onset. Clinical examination showed mainly grade I-II palpebral conjunctival hyperemia, with no cases of grade IV. Most eyes had small papillae measuring less than 1 mm. Tear break-up time was reduced in the majority of eyes. Conclusions: Allergic conjunctivitis in children predominantly affects males and is generally mild to moderate in severity, with itching as the most prominent symptom. Reduced tear break-up time suggests that tear film instability should be considered in management strategies.